Perencanaan Program Penanggulangan Kemiskinan dalam Rangka Memberikan Pelayanan Ekonomi Masyarakat (Studi pada Dinas Sosial Kabupaten Blitar) - Wirasakti, Dicky (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Ponggok is the sub district with the largest poor people in Blitar Regency. According Ministry of Social Affairs data, there are 6,875 KPM BPNT programs. Geographically Ponggok is located in North Blitar which have fertile soil from Kelud eruption. Morphologically Ponggok is connect area between Kediri and Blitar regency so all area can be reached by transportation. Poverty at Ponggok is structural poverty because bad policies. This study aims to determine the process of poverty reduction program planning in Social Service of Blitar Regency. The research method used is qualitative method. Based on the research, the program planning in the Social Service has been suitable according to the stages in the planning theory, and according procedures regulated by Permendagri No.86 of 2017. Some factors that influence the planning process include: human resource planners, social cultural, and system used.